Pengaruh Adaptasi Pakan Terhadap Efisiensi Dan Konversi Pakan Benih Ikan Nemo (Amphiprion sp.) - Juliana Juliana; Hendrik David Julianus Borolla (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2024)
Nemo fish (Amphiprion sp.) is a type of marine ornamental fish that is popular because it is unique in terms of color, shape and movement. Feed is a factor in the growth and survival process of nemo fish. The aim of this research was to determine feed adaptation to the efficiency and feed conversion of nemo fish seeds. The research used an experimental method using a Completely Randomized Design consisting of 3 treatments and 3 replications. Treatment A (silk worms), treatment B (pellets) and treatment C (combination of 70% silk worms and 30% pellets). The best absolute weight growth results were in treatment C, namely 0.33 grams, while the lowest were in treatment B, namely 0.28. The survival rate (SR) during maintenance in each treatment was 100%. The best feed efficiency was in treatment C at 16.17% and the best feed conversion ratio was in treatment C with the lowest conversion ratio value of 4.81. Based on the results of the research conducted, it was concluded that feed adaptation for nemo fish seeds did not have a real influence on the efficiency and feed conversion of nemo fish seeds (Sig. > 0.05).